Finite element analysis to assess the biomechanical behavior of a finger model gripping handles with different diameters - Tony Benedict Jain A.R; Alphin Masilamany S. (Sciendo, 2019)
Study aim: Interactions between the fingers and a handle can be analyzed using a finite element finger model. Hence, the biomechanical response of a hybrid human finger model during contact with varying diameter cylindrical handles was investigated numerically in the present study using ABAQUS/CAE.